2023
DOI: 10.1038/s41598-023-30448-8
|View full text |Cite
|
Sign up to set email alerts
|

Short term results in a population based study indicate advantage for laparoscopic colon cancer surgery versus open

Abstract: The aim of this study was to compare LAP with OPEN regarding short-term mortality, morbidity and completeness of the cancer resection for colon cancer in a routine health care setting using population based register data. All 13,683 patients who were diagnosed 2012–2018 and underwent elective surgery for right-sided or sigmoid colon cancer were included from the Swedish Colorectal Cancer Registry and the National Patient Registry. Primary outcome was 30-day mortality. Secondary outcomes were 90-day mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…A population-based study conducted in Sweden compared laparoscopic (LAP) and open (OPEN) surgeries for colon cancer, revealing the advantages of LAP in terms of short-term mortality, morbidity, and completeness of cancer resection. 13 This finding is consistent with our present study, which focused on laparoscopic procedures Riaz Ahmad et al and reported low mortality rates and favorable shortterm outcomes. Furthermore, laparoscopic surgery for colon cancer has been extensively researched and proven to be oncologically safe, offering various benefits such as reduced blood loss, less pain, shorter hospital stays, and improved quality of life compared to open surgery.…”
Section: Discussionsupporting
confidence: 94%
“…A population-based study conducted in Sweden compared laparoscopic (LAP) and open (OPEN) surgeries for colon cancer, revealing the advantages of LAP in terms of short-term mortality, morbidity, and completeness of cancer resection. 13 This finding is consistent with our present study, which focused on laparoscopic procedures Riaz Ahmad et al and reported low mortality rates and favorable shortterm outcomes. Furthermore, laparoscopic surgery for colon cancer has been extensively researched and proven to be oncologically safe, offering various benefits such as reduced blood loss, less pain, shorter hospital stays, and improved quality of life compared to open surgery.…”
Section: Discussionsupporting
confidence: 94%